The Issue Of Translating Phraseological Units Related To The Lexeme Of Clothing With National-Cultural Characteristics - Sodiqov Dilshodbek Kobilovich (Global Scientific Publishing, 2024)
Nowadays, the fast-evolving linguistic-cultural field in linguistics demands researchers to analyze words, idiomatic expressions, or sentences from different languages. This necessitates a deep exploration of the traditions and mindset of each culture. The vocabulary related to clothing can also serve as a significant element of national cultural identity, as every culture has its own set of idiomatic expressions tied to the concept of traditional attire
Keywords: linguo-cultural direction; national-cultural customs; national cultural clothing lexeme